(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdaUd GdKGdK eeG Hfj Ydjg cJGH GdJLGQI aj GdNjGQ GdPj gh HeYfi GdNjQI, gj ceTjFI aj JQLjM CMO GdWQajf EdG Cf GdeQGO Hg gfG edc CbQGQ GdYbO hEf (B.. (3eOI eYdheIs
(3BNQgG (B:s
(3BNQgG(B: (3hHGdLedI eJi bGe GMJeGd GdaQb hLH GdYed Ydi ebJVi GdbhGYO hGdVhGHW ChLH Gddg dfG cJGHI Pdc aj UMGFa GdMSGf hCbGdfG ef ehHbGJ GdYKQGJs
(3GdfSNI ebGHdI Ydi eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis